Connectedness and well‐being in simulated nature. Issue 2 (4th October 2021) - Pasca, Laura; Carrus, Giuseppe; Loureiro, Ana; Navarro, Óscar; Panno, Angelo; Tapia Follen, César; Aragonés, Juan Ignacio
Abstract: People relate to nature physically, cognitively and emotionally, and this relationship fosters their well‐being. There are several types of environments that vary according to their degree of naturalness, raising the question of whether they each exert different effects on people, connectedness and well‐being. In order to study the extent to which environmental connectedness and well‐being are a function of viewing different types of nature, we conducted a study with 454 participants from five different countries, who viewed images on a computer screen of one of three types of environment (totally natural, quasi‐natural or non‐natural) and responded to a series of associated items. The results of a mediation analysis showed an indirect effect of type of environment on well‐being through positive and negative affect and connectedness to nature. The corresponding ANOVAs revealed differences in the connectedness and well‐being elicited by different types of environment, and in preference: totally natural and quasi‐natural environments (with no differences between them) showed differences with non‐natural environments. Therefore, our study results suggest the usefulness of images of natural environments in fostering people's well‐being and connectedness to nature.